Predictors of myopic macular degeneration in a 12-year longitudinal study of Singapore adults with myopia - Foo, Li Lian; Xu, Lingqian; Sabanayagam, Charumathi; Htoon, Hla M; Ang, Marcus; Zhang, Jingwen; Ohno-Matsui, Kyoko; Cheng, Ching Yu; Hoang, Quan V; Tan, Chuen-Seng; Saw, Seang-Mei; Wong, Chee Wai (British journal of ophthalmology, 2023)
PurposeTo investigate the predictive factors for myopic macular degeneration (MMD) and progression in adults with myopia.MethodsWe examined 828 Malay and Indian adults (1579 myopic eyes) with myopia (spherical equivalent (SE) ≤–0.5 dioptres) at baseline who participated in both baseline and 12-year follow-up visits of the Singapore Malay Eye Study and the Singapore Indian Eye Study. Eye examinations, including subjective refraction and axial length (AL) measurements, were performed. MMD was graded from fundus photographs following the Meta-Analysis for Pathologic Myopia classification. The predictive factors for MMD development and progression were assessed in adults without and with MMD at baseline, respectively as risk ratios (RR) using multivariable modified Poisson regression models. The receiver operating characteristic curve was used to visualise the performance of the predictive models for the development of MMD, with performance quantified by the area under the curve (AUC).ResultsThe 12-year cumulative MMD incidence was 10.3% (95% CI 8.9% to 12.0%) among 1504 myopic eyes without MMD at baseline. Tessellated fundus was a major predictor of MMD (RR=2.50, p<0.001), among other factors including age, worse SE and longer AL (all p<0.001). The AUC for prediction of MMD development was found to be 0.78 (95% CI 0.76 to 0.80) for tessellated fundus and increased significantly to an AUC of 0.86 (95% CI 0.84 to 0.88) with the combination of tessellated fundus with age, race, gender and SE (p<0.001). Older age (p=0.02), worse SE (p<0.001) and longer AL (p<0.001) were found to be predictors of MMD progression.ConclusionsIn adults with myopia without MMD, tessellated fundus, age, SE and AL had good predictive value for incident MMD. In adults with MMD, 1 in 10 eyes experienced progression over the same period. Older age, more severe myopia and longer AL were independent risk factors for progression.